Feasibility of Emotional Freedom Techniques in Patients with Posttraumatic Stress Disorder: a pilot study - Yujin Choi; Yunna Kim; Do-Hyung Kwon; Sunyoung Choi; Young-Eun Choi; Eun Kyoung Ahn; Seung-Hun Cho; Hyungjun Kim (Korean Pharmacopuncture Institute, 2024)
Objectives: Posttraumatic stress disorder (PTSD) is a prevalent mental health condition, and techniques using sensory stimulation in processing traumatic memories have gained attention. The Emotional Freedom Techniques (EFT) is a psychotherapy that combines tapping on acupoints with exposure to cognitive reframing. This pilot study aimed to assess the feasibility of EFT as a treatment for PTSD by answering the following research questions: 1) What is the compliance and completion rate of patients with PTSD with regard to EFT protocol? Is the dropout rate reasonable? 2) Is the effect size of EFT protocol for PTSD sufficient to justify a future trial?Methods: Thirty participants diagnosed with PTSD were recruited. They received weekly EFT sessions for five weeks, in which they repeated a statement acknowledging the problem and accepting themselves while tapping the SI3 acupoint on the side of their hand. PTSD symptoms were evaluated using the PTSD Checklist for DSM-5 (PCL-5) before and after the intervention.Results: Of the 30 PTSD patients (mean age: 34.1 ± 9.1, 80% female), 96.7% showed over 80% compliance to the EFT sessions, and 86.7% completed the entire study process. The mean PCL-5 total score decreased significantly after the intervention, with a large effect size (change from baseline: -14.33 [95% CI: -19.79, -8.86], p < 0.0001, d = 1.06).Conclusion: The study suggests that EFT is a feasible treatment for PTSD, with high session compliance and low dropout rates. The effect size observed in this study supports the need for a larger trial in the future to further investigate EFT as a treatment for PTSD. However, the lack of a control group and the use of a self-rated questionnaire for PTSD symptoms are limitations of this study. The findings of this pilot study can be used to plan a future trial.